Development of wearable electromyogram (EMG) device for upper extremity in aerobic exercise - Zulkifli, Ahmad@Manap; Ummu Kulthum, Jamaludin; Aishah, A. F. Q. A.; Najeb, J. M. (IOP Publishing, 2019)
The demand on the wearable device in sport for health monitoring is increasing due to the awareness among the people while they undergo any physical activities. Therefore, the purpose of this study is to develop a wearable surface electromyogram device that can be used to measure and to monitor muscle activity during aerobic exercise. A 10-bit analog to digital converter (ADC) micro-controller board is selected to obtain and process the data sensed by Ag/AgCl wet electrodes. The obtained data is transmitted to the computer via Bluetooth's wireless technology using HC-05 master-slave module. In prior, the wearable is attached to the palmaris longus muscle in two different activities known as isometric and isotonic contractions. The fourth-order Butterworth filter is applied to eliminate the noise and filtering the raw signal in order to produce a clean EMG signal. Then, the device is compared with the commercial EMG to validate the signal obtained and to ensure the result is reliable. The results reveal that the high consistency of the voltage amplitude is successfully achieved in the high reliability of exercise voluntary contractions especially for isotonic and isometric. These types of contraction are distinguished able from the pattern of signal. The error of signal analysis is < 5% in validity test verified the accuracy of this device compared with the other device available in the market. This device is potentially can be used for upper extremity of aerobic exercise in measuring the muscle contraction, and it is beneficial for the biomedical and sports application environment.